Analisis Kinerja Sosial dan Kinerja Keuangan Lembaga Keuangan Mikro (LKM) Usaha Ekonomi Desa-Simpan Pinjam (UED-SP) Badan Usaha Milik Desa (BUMDes) Ngaso Mandiri Desa Ngaso Kecamatan Ujung Batu Kabupaten Rokan Hulu - Perdana T, Pieter; Rifai, Ahmad; Muwardi, Didi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
UED-SPis a part of the Program Pengembangan Desa (PPD) in Riau Province aims to prevent and reduce poverty in village. The purpose of this research is to analyze the performance of social and financial UED-SP BUMDes Ngaso Mandiri Ngaso Village Ujung Batu district Rokan Hulu Regency. Analyzed using reachment and PEARLS analysis to assess financial performance 2008-2012. The results of this research showing the social performance of the range 1) fluctuated productivity staff, 2) fluctuated custumers number, 3) increasing the participation of women custumers , 4) distribution of loans in employment dominated by trade sector and 5) increased public awareness to save . Financial performance show rates of Protection isn’t ideal,rates of Effective Financial Structure at a rates of current assets, debt ratio , capital ratio indicates in ideal conditions , while the rates of savings ratio and loans outstanding indicates conditions are not ideal . Rates of Asset Quality in calculation of NPL are in ideal conditions and the rates of non productive assets in ideal conditions. Rates of Return and Costs in calculation of return ratio loans are in ideal conditions, the rates of operating expenses not in ideal conditions and the rates of net income to be in ideal conditions. Rates of Liquidity at a ratio of current assets not produce are not ideal.Signs of Growth Ratio in the calculation of asset growth, deposits and custumers institution are in ideal condition while capital growth and loans outstanding growth is not ideal. Keywords: UED-SP Microfinance Institution, Social and Financial Performance